UPAYA PENINGKATAN MINAT DAN HASIL BELAJAR MATEMATIKA MATERI FPB DAN KPK MELALUI MEDIA PAKONTA DENGAN TEORI DIENES - dinda dwi pangestu ningrum; Anissa Niken Tina Paramitha (Pedir Research Institut, 2021)
This study aims to increase students' interest and learning outcomes in mathematics, especially FPB and KPK materials, using Pakonta media and Dienes theory. This study uses qualitative research methods using the literature review method, the causes that cause a lack of interest and low learning outcomes of students in learning Mathematics, especially FPB and KPK are due to lack of understanding of students regarding material descriptions or learning concepts besides that many students consider mathematics learning is a difficult and boring learning and so on. Through Pakonta media with Dienes theory, a pleasant atmosphere will be created, not boring, besides that students will be easier to understand the material presented. In this case, the role of educators is also very important in motivating, designing learning as attractive as possible to increase interest in learning and student learning outcomes in learning mathematics, especially FPB and KPK.